Dental service sector and patient-reported oral health outcomes: Modification by trust in dentists - Song, Youngha; Santiago, Pedro; Nair, Rahul; Cho, Hyun-Jae; Brennan, David (Frontiers in Public Health, 2023)
Objective: To examine the association of patient-reported oral health outcomes with dental service sector and trust in dentists. A possible interaction effect of trust on the association was also explored. Methods: Randomly selected adults aged 18+ years living in South Australia were surveyed with self-complete questionnaires. Outcome variables were self-rated dental health and the Oral Health Impact Profile. Dental service sector and the Dentist Trust Scale were included in bivariate and adjusted analyses with sociodemographic covariates. Results: Data were analyzed from 4,027 respondents. Unadjusted analysis showed that poor dental health and oral health impact were associated with sociodemographic characteristics including lower income/education, public dental service, and lower trust in dentists (p<0.01). Adjusted associations were similarly maintained (p<0.05) but attenuated with the loss of statistical significance mainly in trust tertiles. Lower trust in dentists in private sector had an interaction effect with a higher prevalence ratio of oral health impact (PR=1.51; 95% CI 1.06–2.14; p<0.05). Conclusions: Patient-reported oral health outcomes were associated with sociodemographic characteristics, dental service sector, and trust in dentists. Implications for public health: The inequality of oral health outcomes between dental service sectors needs to be addressed both independently and in association with covariates including socioeconomic disadvantage.